Analisis Pengaruh Kualitas Iklan Media Sosial Youtube Terhadap Loyalitas Konsumen Pada Iklan Ramayana Department Store - Regita Cahyani Pramesti; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Youtube is one of a social media platform to conduct promotions. In this research, Ramayana Department Store uses Youtube as a marketing tool through their interesting adveritsements that caught a lot of Youtube users' attention. The objective of this research is to discover the impact of social media promotions against the loyalty of consumers. Data collection is conducted against 120 respondents that meets the criteria; in which the respondents of this research are Youtube users who have watched Ramayana Department Store's advertisements and have purchased a transaction at least once in all of Ramayana Department Store's outlets all over Indonesia. After the data is acquired, there will be further analysis using multiple linear regression. The analysis for this research will be done by using a SPSS statistic software. The result shows that the variables of advantageous campaign, popular content, relevant content, and frequently update content indicates significant impact against dependent variable that is consumers' loyalty. However, the variable of varous platform and offers application has no significant influence against the dependent variable that is consumers' loyalty.